Polarographic Studies and Thermodynamic Behaviour of Cd(II) Complexes with Thiophene-2-acetate - lal Prathihar, Panna; Mukherji, S.K.; Singh, R.V. (Asian Journal of Chemistry, 2010)
Polarographic studies and thermodynamic behaviour of Cd(II) complexes with thiophene-2-acetate have been studied. In this system cadmium(II) reduces reversibly with the involvement of two electrons, as the slopes of plots of log vs. Ed.e. varied within 31 ±2 mV. The diffusion controlled nature of reduction was revealed from the straight line plots of id vs. The overall formation constants were determined by DeFord method. It was found that there was no change in the number of species formed by increasing the temperature from 30 to 40ºC but the stability constants of the complexes decreased with rise in temperature. The negative enthalpy change in Cd-thiophene-2-acetate also confirmed the complex formation.